2009
DOI: 10.1143/jjap.48.04c023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dissolved Oxygen on Cu Corrosion in Single Wafer Cleaning Process

Abstract: We investigated Cu corrosion at the via bottom of multi-layered Cu interconnects that occurred after post-etching wet cleaning and caused via open failures. We found that oxygen was dissolved into de-ionized water (DIW) on the wafer edge from the air atmosphere during the rinse step after chemical cleaning and that Cu was oxidized due to the high oxidation-reduction potential (ORP) of the rinse DIW. To prevent Cu interconnects from being corroded, control of the dissolved oxygen and the ORP of the rinse DIW by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 3 publications
1
15
0
Order By: Relevance
“…Copper reacts with dissolved oxygen and forms at first cuprous oxide which reacts with oxygen to procedure cupric oxide. These copper oxides react with the available anions in the vicinity to form compounds further (Imai et al, 2009;Lee et al, 2016;Zakowski et al, 2014). The time delay in the formation of copper oxides and development period of the patina in stable state might be the reason for the highest corrosion rate to be occurred at the initial attack period.…”
Section: Figurementioning
confidence: 99%
“…Copper reacts with dissolved oxygen and forms at first cuprous oxide which reacts with oxygen to procedure cupric oxide. These copper oxides react with the available anions in the vicinity to form compounds further (Imai et al, 2009;Lee et al, 2016;Zakowski et al, 2014). The time delay in the formation of copper oxides and development period of the patina in stable state might be the reason for the highest corrosion rate to be occurred at the initial attack period.…”
Section: Figurementioning
confidence: 99%
“…Imai et al [ 21 ] investigated the effect of dissolved oxygen in DIW on the corrosion of Cu during the wafer-cleaning process and revealed that the etch rate of Cu increased as the dissolved oxygen increased. They reported that the Cu surface was ionized by DIW with a high dissolved-oxygen content.…”
Section: Resultsmentioning
confidence: 99%
“…They reported that the Cu surface was ionized by DIW with a high dissolved-oxygen content. The oxidation mechanism of copper by dissolved oxygen is as follows [ 21 ]: …”
Section: Resultsmentioning
confidence: 99%
“…Copper reacts with dissolved oxygen and forms at first cuprous oxide which reacts with oxygen to procedure cupric oxide. These copper oxides react with the available anions in the vicinity to form compounds further (Imai et al, 2009;Zakowski et al, 2014). The time delay in the formation of copper oxides and development period of the patina in stable state might be the reason for the highest corrosion rate to be occurred at the initial attack period.…”
Section: Figurementioning
confidence: 99%
“…Figure 3: Corrosion rate against corrosion period for the variation of operating temperature with the river water flow velocity of 1.0 / After 30 days of operations, corrosion rates are found to be almost steady showing minimum values.Copper reacts with dissolved oxygen and forms at first cuprous oxide which reacts with oxygen to procedure cupric oxide. These copper oxides react with the available anions in the vicinity to form compounds further(Imai et al, 2009;Zakowski et al, 2014). The time delay in the formation of copper oxides and development period of the patina in stable state might be the reason for the highest corrosion rate to be occurred at the initial attack period.The thermal effect on corrosion rate is as like that of weight loss, i.e., higher corrosion rate is witnessed for higher operating temperature.…”
mentioning
confidence: 99%